Human T-Cell Lymphotropic Virus Type 1 and Strongyloides stercoralis Co-infection: A Systematic Review and Meta-Analysis - Ye, Lingqing; Taylor, Graham P.; Rosadas, Carolina (Frontiers in Medicine, 2022)
Background: The distribution of human T cell lymphotropic virus type 1 (HTLV-1) overlaps with that of Strongyloides stercoralis. S stercoralis infection has been reported to be impacted by co-infection with HTLV-1. Disseminated strongyloidiasis and hyperinfection syndrome, which are commonly fatal, are observed in HTLV-1 co-infected patients. Reduced efficacy of anti-strongyloidiasis treatment in HTLV-1 carriers has been reported. The aim of this meta-analysis and systematic review is to better understand the association between HTLV-1 and S. stercoralis infection. Methods: PubMed, Embase, MEDLINE, Global Health, Healthcare Management Information Consortium databases were searched. Studies regarding the prevalence of S. stercoralis, those evaluating the frequency of mild or severe strongyloidiasis, and treatment response in people living with and without HTLV-1 infection were included. Data were extracted and odds ratios were calculated. Random-effect meta-analysis was used to assess the pooled OR and 95% confidence intervals. Results: Fourteen studies were included after full-text reviewing of which seven described the prevalence of S. stercoralis and HTLV-1. The odds of S. stercoralis infection were higher in HTLV-1 carriers when compared with HTLV-1 seronegative subjects (OR 3.2 95%CI 1.7-6.2). A strong association was found between severe strongyloidiasis and HTLV-1 infection (OR 59.9, 95%CI 18.1-198). Co-infection with HTLV-1 was associated with a higher rate of strongyloidiasis treatment failure (OR 5.05, 95%CI 2.5-10.1). Conclusion: S. stercoralis infection is more prevalent in people living with HTLV-1. Co-infected patients are more likely to develop severe presentation and to fail treatment. Screening for HTLV-1 and Strongyloides sp. should be routine when either is diagnosed.